Antihelmintic Treatment And Strategy To Eliminate Soil-Transmitted Helminth In Children - Sacharissa Zerlina Tsarwah Thirafi; Zaky Firmawan El-Hakim; Lutfi Dewanda Nugroho; Ayush Khangai; Dwiyanti Puspitasari (Biomolecular and Health Science Journal, 2021)
Introduction: Soil-transmitted helminthiasis (STH) is one of the neglected tropical diseases. These worm infections contributed to global child health. Children suffer from chronic disease and fail to reach their full physical and intellectual capacity. Antihelmintic treatment or deworming is recommended for controlling STH. World Health Organization is focusing predominantly on deworming school-age children. Even antihelmintic treatment has to be repeated regularly, children can reinfect if their environment contaminated. It needs a strategy to control STH and treating adults as well as a child.Methods: We searched the literature for relevant clinical research and articles using Google Scholar and PubMed which were published between 2014 and 2018 with keywords “soil-transmitted helminths”, “soil-transmitted helminthiasis”, combined with “eradication” and “elimination”. We excluded research and article which were not written in English. Our study included a total number of ten publications.Results: The studies mentioned that antihelmintic requires the control of STH transmission and need for the treatment in different age groups.Conclusion: According to our findings, the mass drug administration is recommended as a control strategy in both low and middle-income countries to reduce helminthiasis and schistosomiasis. High STH reinfection rate requires an integrated approach including the use of safe pure water, improvement for personal hygiene and sanitation, proper toilets, and reducing the practice of defecation in nature. The previous studies showed that studies focused on deworming using antihelmintic